Pelatihan Digital Marketing Bagi Kelompok Umkm Di Nagari Tiku Selatan, Kabupaten Agam - Ayu, Rindang; Oktarisa, Fidia; Santoso, Indriyani (Universitas Negeri Padang, 2025)
Business development in the digital era requires UMKM entrepreneurs skilled in digital technology to have a digital strategy in product promotion and marketing. Some business units have promoted and marketed their products on social media and e-commerce, but not consistently. This indicates a lack of interest in using digital media to develop their businesses. Enrichment activities and training in product promotion and marketing using social media are needed so that UMKM can compete and increase sales in the digital era. This study provided practical digital marketing training to 20 UMKM entrepreneurs in Nagari Tiku Selatan Agam. The activities consisted of enrichment in the form of delivering material on the importance of digital marketing and direct practice in optimizing social media through basic advertising, Google My Business, marketplaces, and WhatsApp Business. The results of the training implementation showed that some MSME entrepreneurs were able to create social media accounts that had never been used before in digital marketing, create attractive marketing content designs using applications practiced in the workshop, and upload directly to their respective business media accounts.